Percepția fenomenului corupției în instituțiile publice - Novak, Andrei (Calitatea Vieții, 1994)
The author synthesizes the results of a survey made in July 1993 by ICCV, concerning the perception of the quality of social-political environment. The major topic was building up a meaningful model of the way people picture out the phenomenon of corruption at the present moment.